2016
DOI: 10.1111/jfpp.12881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Shrinkage Effect on the Modeling Kinetics of Osmotic Dehydration of Sweet Potato (Ipomoea batatas (L.))

Abstract: The kinetics of water loss (WL), solid gain (SG) and water activity (a w ) of the osmotic dehydration of sweet potato (Ipomoea batatas (L.)) slices were investigated. Three osmotic solutions, sucrose, sorbitol and fructose, were used with two different water activities, 0.900 and 0.940. The diffusivities of both water and solute were evaluated by using Crank's analytical solution to Fick's second law and according to the models of Azuara and Barbosa J unior et al. The shrinkage effect was considered to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
4
25
0
3
Order By: Relevance
“…Although the effective diffusivity varies with the food material and the experimental conditions, which makes comparison difficult in terms of exact values, the D eff obtained according to Fick's model presented the analogous order of magnitude of food materials subjected to the OD (Bahmani et al, 2016;Junqueira et al, 2017c;Mendonça et al, 2017;Souraki et al, 2014). Table 2, Fick's model showed lower R 2 values (even 0.640) which indicates its low acuity in portraying the experimental data.…”
Section: Mathematical Modelingmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the effective diffusivity varies with the food material and the experimental conditions, which makes comparison difficult in terms of exact values, the D eff obtained according to Fick's model presented the analogous order of magnitude of food materials subjected to the OD (Bahmani et al, 2016;Junqueira et al, 2017c;Mendonça et al, 2017;Souraki et al, 2014). Table 2, Fick's model showed lower R 2 values (even 0.640) which indicates its low acuity in portraying the experimental data.…”
Section: Mathematical Modelingmentioning
confidence: 95%
“…The Fito and Chiralt hydrodynamics model (Fito & Chiralt, 1997) considers an equilibrium approach (Equation 6): driving force between the product and the hypertonic solution is the strongest, and as the osmotic process extends, an osmotic pressure reduction occurs, due to mass transfer between the phases (Junqueira et al 2017c;Lombard et al, 2008;Ramya & Jain, 2017).…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Volume reduction brings significant shrinkage and subsequently low porosity due to which the final dried product bears poor rehydration ability (Aral & Beşe, ).The removal of water from plant cells causes shrinkage which changes its physical properties and affect the rehydration of dried product (Junqueira, Corréa, & Mendonça, ). Doymaz and Ismail () studied the rehydration of pretreated dried bell pepper samples at three different rehydration temperature (25, 50, and 75°C) and found that diffusion coefficient of bell peppers increased with increasing rehydration temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Shrinkage and rehydration characteristics of any food material are significantly influenced by the drying methods (Doymaz & Ismail, ; Joardder et al, ; Junqueira, Corréa, & Mendonça, ). The osmotic properties of plants cell wall diminishes due to shrinkage during drying process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation